2007
DOI: 10.1055/s-0039-1698341
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Expression Correlates with the Level of Inflammation in Periapical Cysts

Abstract: Objectives In an attempt to elucidate if inducible nitric oxide expression (iNOS) is correlated with the level of inflammation in periapical cysts with accuracy, the goal of this study was to evaluate the expression of iNOS in these ones. Methods 30 cases were included in this study being iNOS evaluated by means of immunohistochemistry. Statistical analysis was performed by Kruskal-Wallis non-parametric test followed by the post-hoc Dunn’s test. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[ 20 ] Keratocyst is different from other odontogenic cyst. Matsumoto and Ribeiro[ 62 ] indicated that immunoreactivity of inducible nitric oxide expression was expressed in several cellular types present in periapical cyst, being positively correlated with the level of inflammation. Therefore, inducible nitric oxide expression plays an important role in the pathogenesis of periapical cysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] Keratocyst is different from other odontogenic cyst. Matsumoto and Ribeiro[ 62 ] indicated that immunoreactivity of inducible nitric oxide expression was expressed in several cellular types present in periapical cyst, being positively correlated with the level of inflammation. Therefore, inducible nitric oxide expression plays an important role in the pathogenesis of periapical cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto and Ribeiro[ 62 ] reported that the value of fine-needle aspiration biopsy in cystic lesions of the maxillofacial region is found as successful as in the solid lesions.…”
Section: Discussionmentioning
confidence: 99%